2016
DOI: 10.1080/09712119.2016.1214136
|View full text |Cite
|
Sign up to set email alerts
|

The effects of access to pasture on growth performance, behavioural patterns, some blood parameters and carcass yield of a slow-growing broiler genotype

Abstract: The aim of the present study was to determine the effects of access to a pasture on growth performance, behavioural patterns, some blood parameters and carcass yield of a slow-growing broiler genotype. A total of 210 one-day-old male chicks of Hubbard ISA Red JA were used in the experiment. At the 84th day, live weight was determined to be lower in the outdoor rearing system (P < .01). Better feed conversion ratio was found in the indoor rearing system (P < .01). The behaviour of the broilers was compared by o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 18 publications
5
10
0
Order By: Relevance
“…Overall, the rectal temperatures of broiler chickens in this study were still in the normal range of 41.55°C-41.95°C as reported by Aengwanich and Simaraks (2004) and Attia et al (2011). Similar to our findings, Ipek and Sozcu (2017) reported the rectal temperature of broilers with or without access to pasture were closely related.…”
Section: Discussionsupporting
confidence: 90%
“…Overall, the rectal temperatures of broiler chickens in this study were still in the normal range of 41.55°C-41.95°C as reported by Aengwanich and Simaraks (2004) and Attia et al (2011). Similar to our findings, Ipek and Sozcu (2017) reported the rectal temperature of broilers with or without access to pasture were closely related.…”
Section: Discussionsupporting
confidence: 90%
“…Ponte et al (2008b) reports that broilers with pasture access have improved performance compared to those without pasture access. Conversely, Ipek and Sozcu (2017) observed decreased performance of broilers with pasture access compared to conventionally reared broilers, while Moyle et al (2014) reported no growth differences between pasture and nonpasture raised broilers.…”
Section: Introductionmentioning
confidence: 82%
“…Fanatico et al (2009) and Moyle et al (2014) also reported similar results in fast-growing broilers with or without access to pasture. However, in slow-growing broiler chickens, Ipek and Sozcu (2017) reported that chickens with access to pasture had lower breast and abdominal fat yields compared to their counterparts raised conventionally with no access to pasture. The current study focused on the utility of Brazil nut as a substitute for synthetic Met in different phases of organic broiler chicken feed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Broiler and organic production systems were developed following a tendency of concerns focused on human health and nutrition (Stadig et al, 2016;Ipek & Sozcu et al, 2017). Consumers attribute higher quality and safety to the meat obtained in these alternative systems This kind of breeding is also associate to excellent levels of animal welfare (Castromán et al, 2013).…”
Section: Introductionmentioning
confidence: 99%